PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA PENUMPANG MRT JAKARTA (Universitas Teknologi Muhammadiyah Jakarta (UTM Jakarta), 2019)
This study aims to analyze the effect of service quality on customer satisfaction in the Jakarta MRT transportation service business. The sampling technique used was purposive sampling of 100 people who have used or routinely used the MRT as a research sample. The data analysis method used is a quantitative analysis of the validity and reliability test, the classic assumption test, linear regression analysis, t test and F test and the coefficient of determination. Based on data analysis, the results of the study indicate that the indicators in this study are valid and reliable. In the classical assumption test that the data is normally distributed, there is no heteroscedasticity and multicollinearity. The results obtained from SPSS data processing, it can be concluded that Service Quality has a positive influence on the MRT Jakarta Customer Satisfaction. These results show empirical evidence that the better the quality of service, the MRT customer satisfaction will increase.